2019
DOI: 10.1007/s12264-018-00333-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gastrodin on Early Brain Injury and Neurological Outcome After Subarachnoid Hemorrhage in Rats

Abstract: Gastrodin is a phenolic glycoside that has been demonstrated to provide neuroprotection in preclinical models of central nervous system disease, but its effect in subarachnoid hemorrhage (SAH) remains unclear. In this study, we showed that intraperitoneal administration of gastrodin (100 mg/kg per day) significantly attenuated the SAH-induced neurological deficit, brain edema, and increased blood-brain barrier permeability in rats. Meanwhile, gastrodin treatment significantly reduced the SAHinduced elevation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 26 publications
(35 reference statements)
1
22
0
Order By: Relevance
“…Nevertheless, GAS could alleviate motor performance in cerebral palsy patients and rescue cell death in macrophages by inhibiting oxidative stress [ 31 ]. GAS treatment increased blood-brain barrier permeability and attenuated subarachnoid hemorrhage induced brain damage by decreasing the oxidative stress and inflammation in rats [ 6 ]. At present, our results also found that Pb exposure increased MDA level and decreased the activities of SOD and TAC ( Table 2 ), which could contribute to its pathogenesis by disrupting the pro-/antioxidant balance in cells and decreases the activities of several antioxidant enzymes [ 8 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, GAS could alleviate motor performance in cerebral palsy patients and rescue cell death in macrophages by inhibiting oxidative stress [ 31 ]. GAS treatment increased blood-brain barrier permeability and attenuated subarachnoid hemorrhage induced brain damage by decreasing the oxidative stress and inflammation in rats [ 6 ]. At present, our results also found that Pb exposure increased MDA level and decreased the activities of SOD and TAC ( Table 2 ), which could contribute to its pathogenesis by disrupting the pro-/antioxidant balance in cells and decreases the activities of several antioxidant enzymes [ 8 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The choice of Pb dose was based on previous reports [ 8 , 12 ]. The dose of GAS selected in this study was based on previously published data on the neuroprotective effect of GAS [ 1 , 6 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, new insight suggests that EBI within 72 hours after SAH onset may lay the foundation for subsequent pathophysiological changes and poor outcomes of patients. The pathological mechanisms of EBI include oxidative stress, platelet activation, in ammation, and neuronal apoptosis [34][35][36][37]. One animal experiment found that hyperglycemia could increase reactive oxygen species (ROS) production through activating protein kinase C after stroke, thereby exacerbating oxidative stress [38].…”
Section: Discussionmentioning
confidence: 99%
“…Telmisartan [ 225 ], nebivolol [ 226 ] and curcumin [ 227 ] can ameliorate cerebral vasospasm, and Pterostilbene can attenuate EBI by inhibiting the NLRP3 inflammasome [ 228 ]. Some antioxidants (e.g., apigenin [ 229 ], peroxiredoxin1/2 [ 230 ], docosahexaenoic acid [ 231 ], sodium hydrosulfide [ 232 ], cysteamine [ 233 ], gastrodin [ 234 ], naringin [ 60 ], and progesterone [ 235 ]) play a neuroprotective role in EBI through the effects of anti-apoptosis after SAH, but other antioxidants (e.g. AVE 0991 and mangiferin [ 56 , 236 ] memantine [ 59 , 237 ], salvianolic acid B [ 238 , 239 ], salvianolic acid A [ 240 ], and allicin [ 241 ]) protect against SAH-induced oxidative injury via inhibition of oxidative, inflammatory, and apoptotic pathways.…”
Section: Antioxidants and Antidepressants In Stroke/depressionmentioning
confidence: 99%